Pengaruh Modal Pendidikan Kewirausahaan terhadap Pengembangan Keterampilan Kewirausahaan Mahasiswa di Kabupaten Sidoarjo - Abdul Hafidz Rosydi Fuady; Didit Darmawan (Journal of Management and Social Sciences, 2024)
In Indonesian universities, entrepreneurship education is one of the current trends. For this reason, students are required to take all courses on entrepreneurship. So that students can form skills through knowledge and confidence. The purpose of the empirical study is to identify the effect of entrepreneurship education on students' entrepreneurial skills. Research data were collected from students who have carried out the learning process on entrepreneurship at the University of Sidoarjo Regency. This research uses quantitative methods through survey methods to collect data from 100 respondents. The purposive sampling method is used to determine the number of samples. Furthermore, the data will be analyzed using simple linear regression analysis through SPSS. This study can show that entrepreneurship education has a significant influence on the development of students' entrepreneurial skills. The results of the study in higher education can help the entrepreneurship education curriculum to be more developed, the implementation of learning is more systematic and specific with outputs from useful education courses and stronger student entrepreneurial skills.